Oscillations due to time-delayed driving of a ball in a water jet - a challenging problem of the International Physicists' Tournament 2019 - Michalke, Simon; Fösel, Angela; Schmiedeberg, Michael (European Journal of Physics, 2020)
The International Physicists' Tournament (IPT) 2019 dealt with 17 challenging problems. In this article, we present experimental as well as theoretical approaches exemplarily to one of these tasks. A ball placed on a hard and flat surface can show oscillation movement when being hit by a jet of water from above. To explain the oscillations, a theoretical model is introduced and its predictions are compared to the experimental measurements. Furthermore, the structure of the IPT itself is characterized shortly in this article, as well as the idea of a new and innovative seminar which was set up at Erlangen University to prepare and assist students in taking part in International Physicists' Tournament. Furthermore, the educational relevance of physics tournaments like IPT for physics education at university is discussed in detail.<br
Keywords: Physics Competitions; International Physicists' Tournament; German Physicists' Tournament; oscillations; nonlinear dynamics; harmonic oscillator; time-delay